TRANSLATION PROBLEMS WITHIN THE EU CONTEXT - Grietēna, Indra (Vertimo studijos, 2017)
The paper reviews publications by Latvian linguists looking at the main translation problems within the context of the EU between 2005 and 2010. The author analyses the publications from three aspects: general aspects of translation problems and practices within the EU context, particular translation problems, and methodological publications providing guidelines for translators working within the EU context. The author reveals discussions on the ways translation influences language in general, the role of the source language for the development of the target language, and the role and responsibility of a translator at the ‘historical crossroads’. The article discusses a number of EU-specific translation problems, including source language interference, problems of the translator’s visibility and a translation’s transparency, ‘false friends’, and linguistic and contextual untranslatability. The author briefly summarizes the contents of guidelines and manuals for translators working within the EU context, highlighting the main differences between English and Latvian written language practices, literal (word-for-word) translation and the translator’s relationship with the source text. The publications selected and analysed have been published either in conference proceedings or in academic journals from the leading Latvian institutions in the field of translation: Ventspils University College, the University of Latvia, the State Language Commission of Latvia and Translation and Terminology Centre of Latvia.